A mascarada lacaniana: arte e revolução, vertentes possíveis à feminilidade - Maranhão, Mírian Tenório (Universidade do Vale do Rio do Sinos, 2008)
This study aims to discuss how the lacanian masquerade concept is structured from Joan Riviere’s work entitled “Femininity as masquerade”, of 1929. To think women as contributaries of an absence considered not anatomically determined anymore, but culturally constructed, allows it to be reflected about the building of a femininity from the slopes of art and revolution. We purpose a reflection concerning the changes caused by contemporaneity which have influenced the buildings of the feminine identity. In order to do so, exemplifications of the implications of the contemporary in the social bonds were made, taken from the speeches of women who were part of a therapeutical group. Aiming for, in this study above all things, to comprehend the concept that refers to the femininity, from theorizations made by Freud and Lacan in order to connect it to what is vehicled in the contemporary feminine speech.
Keywords: arte; contemporaneidade; feminilidade; feminino; art; contemporaneity; femininity; feminine; Ciências Humanas